Study of resistance mechanism of Alternaria blight (Alternaria brassicicola) by biochemical markers in Indian Mustard (Brassica juncea L. Czern. &Coss.) - Mishra, Anurag; Khan, Nawaz Ahmad; Jha, Ratnesh Kumar; Murugesh, Tamilarasi; Singh, Ashutosh (Frontiers in Plant Science, 2024)
Indian mustard (Brassica juncea) is an important oilseed crop in India. Alternaria leaf spot (Alternaria blight) is incited by the fungus Alternaria brassicicola (Berk) Sacc.Alternaria brassicae. It majorly affects crop production leading to a yield loss of up to 70 %. To circumvent this problem, the study of resistant mechanism and identification of biochemical markers is one of the important strategies for its management. In the present study total of 219 genotypes of Indian mustard with check were screened for Alternaria blight in two seasons. Based on AUDPC score Tten consistently performing genotypes were selected for the screening of biochemical and yield attributes under artificial inoculated conditions of Alternaria brassicicola (Berk) Sacc.Alternaria brassicicola. The result showed a negative correlation between disease and yield attributes. The catalase (CAT) activity was significantly increased in resistant genotypes compared to susceptible ones, indicating the crucial role of CAT in the resistance mechanism. Pathogen infection also increases the total protein content and Alternaria resistant genotype showed the highest total soluble protein while susceptible showed the lowest total soluble protein. These ten genotypes were Formatted: Font color: Red categorized by SSI (stress susceptibility index) and Varuna was identified as tolerant and Giriraj as susceptible genotypes for Alternaria brassicicola (Berk) Sacc..Alternaria brassicicola . Varuna and Giriraj were chosen for quantitative analysis of methionine and tryptophan amino acids from seeds by RP-HPLC (Reverse Phase-High Performance Liquid Chromatography) and showed significant differences in the levels of methionine and tryptophan between the Varuna and Giriraj genotypes. Varuna showed higher methionine and tryptophan content compared to the Giriraj genotype. Higher protein content demonstrated an increase in biotic stress-responsive amino acids, such as methionine and tryptophan, suggesting increased resistance to Alternaria diseases in these high-protein genotypes. These amino acids could be used as biochemical markers for Alternaria resistance of mustard.